Teachers’ and Students’ Perception about Creative Thinking Skills, Immersed Integrated Science Learning, and project-based Learning: A cow dung waste issue - Chansyanah Diawati; Noor Fadiawati; Kartini Herlina (Jurnal Pendidikan dan Pembelajaran Kimia, 2020)
Abstract: The perception of science teachers and students on project-based immersed integrated science learning: A cow dung waste issue. This study aims to describe the perception of science teachers and students about creative thinking skills, immersed integrated science learning, and project-based learning of a cow dung waste issue. The survey method used in this study were interviews and questionnaire techniques. The interviews conducted with 7 science teachers respondents. The questionnaires distributed to 121 respondents of junior high school students in the Jati Agung Subdistrict. The results showed that 85.71% of teacher respondents did not know about immersed integrated model yet. They also have never implemented project-based learning, based on the students’ questionnaires, the teachers only gave assignments to 74.07% of student respondents and did not provide real problem-solving. The environmental problem occurs in Jati Agung Subdistrict is a large number of cow dung that causes pollution on the environment around society’s houses. As many as 71.43% of teacher respondents stated that they already knew about creative thinking. However, the creative thinking skills they knew are not relevant to the Torrance framework. Based on the results, teachers’ and students' perceptions of integrated science learning, project-based learning, and creative thinking skills are not according to their nature.